Analisis Kemampuan Komunikasi Matematis Ditinjau dari Motivasi Belajar Selama Pandemi Covid-19 dan Gender - Riski Sumayanti; Rizki Dwi Siswanto (Universitas Muria Kudus, 2021)
This study aims to analyze and describe students’ mathematical communication skills during online learning in terms of learning motivation during the covid-19 pandemic and gender. The method used is descriptive qualitative. Purposive sampling technique was used to select 6 samples consisting of 1 male subject with high learning motivation, 1 female subject with high learning motivation, 1 male subject with moderate learning motivation, 1 female subject with moderate learning motivation, 1 male subject with low learning motivation and 1 female subject with low learning motivation. The instrument in this study used a learning motivation questionnaire and a test of mathematical communication skills. Data analysis was carried out, namely data categorization and reduction, data presentation, and conclusion drawing. The triangulation technique is carried out by comparing the results of the subject’s communication ability test with the interview as a test of the validity of the data. The conclusion of this study, in total communication skills both oral and written, subjects with moderate and low learning motivation, both male and female, were better than subjects with high learning motivation, both male and female. Mathematical communication skills both oral and in writing, female gender subjects are better than male gender subjects